2000
DOI: 10.1161/01.str.31.7.1621
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cerebral Microcirculatory Changes on Cerebral Blood Flow During Cerebral Vasospasm After Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose-Cerebral microcirculatory changes during cerebral vasospasm after aneurysmal subarachnoid hemorrhage (SAH) are still controversial and uncertain. The aim of this study was to investigate the changes of cerebral microcirculation during cerebral vasospasm and to clarify the roles of microcirculatory disturbances in cerebral ischemia by measuring cerebral circulation time (CCT) and regional cerebral blood flow (rCBF). Methods-In 24 cases with aneurysmal SAH, rCBF studies by single-photon em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
127
2
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(139 citation statements)
references
References 39 publications
7
127
2
2
Order By: Relevance
“…This preliminary inference would be in agreement with previous studies demonstrating dilated parenchymal small arteries and arterioles in the low perfusion area distal to spasm, [11][12][13][14]34 attributed to a possible autoregulatory response. 35,36 The behavior of the microvasculature during CVS has previously attracted considerable interest, although both clinical and experimental studies have produced conflicting results.…”
Section: Discussionsupporting
confidence: 93%
“…This preliminary inference would be in agreement with previous studies demonstrating dilated parenchymal small arteries and arterioles in the low perfusion area distal to spasm, [11][12][13][14]34 attributed to a possible autoregulatory response. 35,36 The behavior of the microvasculature during CVS has previously attracted considerable interest, although both clinical and experimental studies have produced conflicting results.…”
Section: Discussionsupporting
confidence: 93%
“…Additional factors contributing to the deleterious consequences of aneurysmal SAH may include global transient ischemia, early brain injury, disruption of the bloodbrain barrier, and activation of inflammatory pathways (Ostrowski et al, 2006;Prunell et al, 2005). It has now been realized that SAH may also impact small-diameter arteries and arterioles, i.e., those involved in the autoregulation of cerebral blood flow (Hattingen et al, 2008;Ishiguro et al, 2002;Ohkuma et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Additional factors contributing to the deleterious consequences of aneurysmal SAH may include global transient ischemia, early brain injury, disruption of the bloodbrain barrier, and activation of inflammatory pathways (Ostrowski et al, 2006;Prunell et al, 2005). It has now been realized that SAH may also impact small-diameter arteries and arterioles, i.e., those involved in the autoregulation of cerebral blood flow (Hattingen et al, 2008;Ishiguro et al, 2002;Ohkuma et al, 2000).In resistance arteries from healthy animals, vasoconstrictor stimuli such as physiologic increases in intravascular pressure lead to smooth muscle membrane potential depolarization, increased voltage-dependent Ca 2+ channel (VDCC) activity, and elevated global cytosolic calcium (Knot and Nelson, 1998 , the NIH (R01 HL078983, R01 HL078983-05S1, R01 HL44455, R37 DK053832, R01 DK065947, R01 HL098243, R01 HL077378, NCRR P20 RR16435, and P01 HL095488), and the American Heart Association (0725837T, 0725841T, 0815736D). Blood Flow & Metabolism (2011) (Jahromi et al, 2008b).…”
mentioning
confidence: 99%
“…Cerebral microvascular vasospasm may actually be more important in producing cerebral ischemia than conduit vessel vasospasm. 4 In our previous study using a rat model of SAH, 5 we demonstrated that cerebral arterioles after SAH have endothelial dysfunction that could contribute to vasospasm. As a result, cerebral arterioles after SAH demonstrated attenuated response to the endothelium-dependent dilator adenosine diphosphate (ADP) and accentuated constriction to endothelin-1 (ET-1).…”
Section: Objectif : L'isoflurane Est Connu Pour Atténuer La Dilatatiomentioning
confidence: 86%